2017
DOI: 10.3390/f8040131
|View full text |Cite
|
Sign up to set email alerts
|

Red Alder-Conifer Stands in Alaska: An Example of Mixed Species Management to Enhance Structural and Biological Complexity

Abstract: Abstract:There is worldwide interest in managing forests to improve biodiversity, enhance ecosystem services and assure long-term sustainability of forest resources. An increasingly important goal of forest management is to increase stand diversity and improve wildlife and aquatic habitat. Well-planned silvicultural systems containing a mixture of broadleaf-conifer species have potential to enhance stand diversity and provide other ecosystem services earlier than typical even-aged conifer plantations. Here, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 94 publications
1
4
0
Order By: Relevance
“…Our alder-Douglas fir results confirm findings in Deal et al (2017) which showed the inclusion of an N-fixing species with a non-N-fixing species can result in overyielding. This effect was associated with differences in some key functional attributes associated with nutrient cycling as observed in the increased abundance of nirK, niS, amoA AOA and AOB genetic markers in the alder rhizosphere soils.…”
Section: Implications For Tree Species Mixturessupporting
confidence: 89%
“…Our alder-Douglas fir results confirm findings in Deal et al (2017) which showed the inclusion of an N-fixing species with a non-N-fixing species can result in overyielding. This effect was associated with differences in some key functional attributes associated with nutrient cycling as observed in the increased abundance of nirK, niS, amoA AOA and AOB genetic markers in the alder rhizosphere soils.…”
Section: Implications For Tree Species Mixturessupporting
confidence: 89%
“…Growth models, together with stand regeneration, harvesting, and mortality models, are important tools in long-term forest management systems (Andreassen and Tomter 2003). Modeling mono-specific stands has a long history, but modeling mixedspecies forests has received much more attention in the last decades (Porté and Bartelink 2002), due to a worldwide trend in managing such forests to improve the biodiversity and environmental services and to assure long-term sustainable forest resources (Deal et al 2017;del Río et al 2016). The structure, dynamics, and productivity of mixed-species stands depend on both interspecific and intraspecific interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Crop tree release is another practice that enhances individual tree productivity by reducing competition for selected trees via the removal of crowns from nearby trees, and both hemlock and spruce respond to release under alder (Deal and Tappeiner ; Deal et al. ). This could be used in harvested riparian zones to promote large conifers that are suitable for future large wood.…”
Section: Discussionmentioning
confidence: 99%